Modi of the idea of responsibility in socio-cultural circumstances of the mid of the 20th – the beginning of the 21st centuries. Part І - M. M. Rohozha (Ukrainian Cultural Studies, 2018)
The paper deals with socio-cultural factors, terminological collisions and modi of the idea of responsibility in the West European socio-cultural space. Main attention is paid to shaping of the idea of responsibility in socio-cultural circumstances of the mid of the 20th – the beginning of the 21st centuries. The first part of the paper outlines the preliminary history of the modern concept of responsibility, peculiarities of the problem in Aristotle’s "The Nicomachean Ethics" are observed as well as the idea of accountability (imputatio) in ethics of P. Abelard in modi of moral guilt and offense. It is mentioned that in Pre-modern culture idea of responsibility is developed in the context of the freedom of human action, one’s capability to keep an answer for one’s actions and to admit guilt. It is specified that in philosophy of Modernity the notion imputatio is represented in I. Kant’s philosophy. Although Kant did not put the problem of accountability as the cornstone of his philosophy, he had defined conditions for possibility of agent’s accountability in such a way that his ideas are at the background of the main conceptions of responsibility of the 20th century. Further in the paper development of the problem around the term Verantwortung (responsibility) is observed. In particular, M. Weber’s ethics of responsibility (in comparison to ethics of conviction) is analyzed. The paper pays attention to the of H. Arendt’s conception of lost generations, and grounds of the problem of responsibility actualization in the sense of life search of these generations are analyzed. The first part of the paper is finished by the analysis of the conception of guilt and responsibility by K. Jaspers who applied to the problem in the context of comprehension of the axiological space of postwar Germany.